Convolution product of the derivatives of order L by k-order derivatives of the Dirac delta supported in (x-1), (x-a) and (x-n) (Nexo Revista Científica, 2013)
not availableDOI: http://dx.doi.org/10.5377/nexo.v25i2.1023